INFLUENCE OF AQUEOUS EXTRACT APPLICATION ON YIELD GRAIN AND PROTEINE IN SOYBEAN PRODUCTION - Mussa Abdurhman, Asma; Mamlić (Miladinov), Zlatica J; Dozet, Gordana; Cvijanović, Gorica; Đukić, Vojin; Bajagić, Marija; Cvijanović, Vojin (Journal of Agricultural Sciences (Belgrade), 2022)
The aim of this study was to investigate the influence of aqueous plant extracts on grain yield and protein yield in soybeans. The testing was conducted at the Institute of Field and Vegetable Crops in Novi Sad on the seeds of the NS Apolo variety. The foliar application was used for aqueous extracts: above ground part of nettle, above ground part of nettle and comfrey, whole banana fruit, banana peel, onion bulb's leaves, top parts of willow twigs and the top parts of soybean plants. In addition to the untreated control variant, the experiment also included a distilled water control. Control with distilled water will show whether the effect of aqueous plant extracts is due to plant material or water. The plant parts were collected, washed with running water, chopped and immersed in rainwater. After fermentation, the obtained plant extract was filtered. Before foliar treatment of soybean plants, the aqueous extract was diluted with water in a ratio of 1:15. Plants were treated twice. The first treatment was done in the V6, and the second treatment was done in the R1 stage. The results of the analysis showed that the use of aqueous extracts contributed to the increase of grain yield and protein yield. The increase in yield ranged from 9.48% to 15.34% and the increased in protein yield from 9.31% to 16.16%. The best effect was achieved by applying the aqueous extract of the whole banana fruit and the aqueous extract of nettle and comfrey. By applying them in each year, a significantly higher yield was achieved in relation to the control with water.             Key words: aqueous extract, soybean, banana, nettle, comfrey